Factors Influencing the Career Satisfaction of Gig Workers within the Klang Valley - Arthi Ravindran; Hemaloshinee Vasudevan (Journal of Management Studies and Development, 2026)
The gig economy is crucial to Malaysia's labor market, notably in the Klang Valley, where gig workers significantly contribute to sectors like e-hailing and food delivery. Improved career satisfaction among these workers enhances global economic growth and productivity. The issue of inequality between formal and informal gig workers is increasingly recognized, highlighting the growing vulnerability of gig workers. The study focuses on factors affecting career satisfaction, including income, job security, social protection, and the working environment. The study uses a quantitative, descriptive approach grounded in assessing career satisfaction among gig workers. It analyzed survey data from 394 participants through SPSS, based on a non-probability convenience sampling method. A sample size of 394 was determined from an estimated population of 10,000 gig workers in Klang Valley, achieving a response rate of 98.5% at a 95% confidence level. Income stability (H1: t=6.256; p <0.001), job security (H2: t=3.390; p <0.001), social protections (H3: t=2.603; p=0.010) and supportive work environment (H4: t=-0.603; p=0.547) is a significant factor in career satisfaction. The Self-Employment Social Security Scheme (Act 789) has notably influenced the social protection of gig workers in Malaysia since 2017, offering valuable insights for policymakers and industry stakeholders to enhance career satisfaction and well-being, thus fostering sustainable growth in the gig economy.